Light heat insulation material with low heat conductivity coefficient as well as preparation method and application of light heat insulation material
By adding catalyst and fiber reinforcement to the silica gel solution, supercritical drying and hydrophobic treatment, lightweight insulation materials with low thermal conductivity and high hydrophobicity are successfully prepared, solving the high-efficiency insulation and low thermal insulation in the aerospace field. Weight requirements enable efficient pneumatic heating protection and shape customization.
Patent Information
- Application Number
- CN202411491025.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-07
AI Technical Summary
It is difficult to develop a lightweight insulation material with low thermal conductivity to meet the demands of high-efficiency insulation and low weight in the aerospace field, especially in the face of hypersonic aircraft, which is difficult to effectively protect pneumatic heating.
By mixing the acidic catalyst solution and the alkaline catalyst solution with the silica gel solution to form a gel solution, fiber reinforcement, aging, supercritical drying and hydrophobic treatment, aerogel thermal insulation with low thermal conductivity and high hydrophobicity was prepared. Material.
A lightweight insulation material with a thermal conductivity as low as 0.02W/(m·K) and a density between 280-320kg/m3, with a water repellent rate of up to 99.9%, suitable for thermal insulation needs in the aerospace field and can Customize thermal insulation products of different shapes according to the mold shape.
Smart Images

Figure CN119263860A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of thermal insulation materials, and in particular relates to a lightweight thermal insulation material with low thermal conductivity, and a preparation method and application thereof. Background Art
[0002] With the development of aerospace technology, the flight speed of aircraft is constantly increasing, and the service environment is becoming increasingly harsh. An effective thermal protection system can provide sufficient protection for the aircraft structure when it faces severe aerodynamic heating, so that the aircraft is free from the damage of the harsh aerodynamic thermal environment and can maintain safe flight for a longer time. Thermal insulation material is one of the key materials for thermal protection of aircraft. When an aircraft passes through the atmosphere at high speed, it will generate extremely high temperatures due to aerodynamic heating. For example, when a hypersonic aircraft flies in the atmosphere, the temperature of some parts will exceed 1000℃ for a long time, which requires the use of high-efficiency thermal insulation materials with low thermal conductivity for thermal protection.
[0003] In addition, bulk density is also an important parameter when selecting thermal insulation materials in the aerospace field. Considering that the weight of an aircraft directly affects its acceleration performance, maneuverability and range, the use of lightweight materials can significantly reduce the total weight of the aircraft, thereby improving fuel efficiency and load capacity.
[0004] Therefore, based on the comprehensive consideration of thermal conductivity and bulk density, a lightweight thermal insulation material with a low thermal conductivity coefficient is still to be developed to meet the demand for thermal insulation materials in aerospace aircraft. Summary of the invention
[0005] The purpose of the present invention is to provide a lightweight thermal insulation material with low thermal conductivity and a preparation method and application thereof, so as to obtain a lightweight thermal insulation material with excellent thermal insulation performance.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] The present invention provides a method for preparing a lightweight thermal insulation material with low thermal conductivity, comprising the following steps:
[0008] S1. Glue preparation: adding the acidic catalyst solution and the alkaline catalyst solution to the silica gel solution, stirring evenly to obtain a gel solution;
[0009] S2. Impregnating the fiber: Spread the fiber reinforcement flat into the mold, pour the gel solution prepared in S1 into the mold, fully impregnate the fiber reinforcement, seal and let stand after degassing;
[0010] S3. Aging: The mold after standing in S2 is heated for aging;
[0011] S4. Solvent replacement: Immerse the aged wet gel in ethanol in S3 for solvent replacement at least twice; the relationship between the time of each solvent replacement and the thickness d of the wet gel is specifically as follows:
[0012] When d < 10 mm, soak for 1 - 2 days each time; when 10 < d < 20 mm, soak for 4 days each time; when 20 < d < 25 mm, soak for 6 days each time; when 20 < d < 30 mm, soak for 8 days each time.
[0013] S5. Supercritical drying: Perform supercritical carbon dioxide drying on the wet gel after solvent replacement in S4 to obtain an aerogel thermal insulation layer.
[0014] S6. Moisture-proof treatment: Perform gradient high-temperature treatment on the aerogel thermal insulation layer obtained in S5; then place it in a vacuum environment, add a siloxane-based hydrophobic reagent for hydrophobic treatment, and take it out and dry to obtain the thermal insulation material.
[0015] Furthermore, in step S1, the concentration of the acidic catalyst solution is 0.5 - 1.5 mol / L, the concentration of the basic catalyst solution is 3 - 5 mol / L, and the silicon content of the silica gel solution is 15 - 30%.
[0016] Furthermore, in step S1, the mass ratio of the silica gel solution, the acidic catalyst solution, and the basic catalyst solution is 100:(2 - 4):(2 - 4).
[0017] Furthermore, in step S1, the acidic catalyst includes one or more of phosphoric acid, nitric acid, hydrochloric acid, sulfuric acid, acetic acid, oxalic acid, or acetic acid.
[0018] Furthermore, in step S1, the basic catalyst includes one or two of ammonia water, sodium hydroxide, ammonium fluoride, ammonium carbonate, ammonium bicarbonate, and ethylenediamine.
[0019] Furthermore, in step S2, the fibers in the fiber reinforcement include one or more of quartz fiber, basalt fiber, glass fiber, or alumina fiber, preferably quartz fiber.
[0020] Furthermore, in step S2, the standing time is 40 - 60 h, preferably 48 h.
[0021] Furthermore, in step S3, the aging temperature is 75 - 90 °C, and the aging time is 40 - 60 h, preferably 48 h.
[0022] Furthermore, in step S5, the temperature of the supercritical drying is 40 - 60 °C, and the pressure is 10 - 14 MPa.
[0023] Furthermore, in step S6, the specific process of the gradient high temperature treatment is: heating from 50°C to 200-250°C and then keeping it warm for at least 2 hours, then heating to 600-700°C and then keeping it warm for at least 1 hour, and the heating rate is 2-5°C / min.
[0024] Further, in step S6, the siloxane hydrophobizing agent includes one or more of trimethylmethoxysilane, trimethylethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, dimethylmethoxysilane, dimethylethoxysilane, methyltrimethoxysilane or methyltriethoxysilane.
[0025] Furthermore, the hydrophobic treatment time is 40-60 hours, preferably 48 hours.
[0026] The invention also provides a lightweight heat-insulating material with low thermal conductivity prepared by the preparation method.
[0027] Furthermore, the thermal conductivity of the thermal insulation material is 0.020-0.025 W / (m·K).
[0028] Furthermore, the density of the thermal insulation material is 280-320 kg / m 3 .
[0029] Furthermore, the water repellency of the thermal insulation material is not less than 99.5%.
[0030] The present invention also provides a lightweight thermal insulation material with low thermal conductivity for use in aerospace, shipbuilding or military fields, such as aircraft, missile warheads and other application scenarios that require thermal insulation, lightness and hydrophobicity.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] (1) The present invention successfully prepares a lightweight thermal insulation material with low thermal conductivity and high hydrophobicity through the steps of gelation, dipping, aging, solvent replacement, supercritical drying, high temperature treatment, and hydrophobic treatment.
[0033] (2) The present invention combines the preparation method of aerogel composite materials, and obtains a lightweight insulation material with low density and low thermal conductivity by compounding a commonly used silica gel solution and a fiber reinforcement. The thermal conductivity can be as low as 0.02W / (m·K).
[0034] (3) The present invention fully considers the relationship between the solvent replacement time and the wet gel thickness during the preparation process, and can specifically adjust the solvent immersion replacement time according to the thickness parameters of different gels.
[0035] (4) The present invention performs hydrophobic treatment on the prepared thermal insulation material, and the hydrophobicity of the thermal insulation material finally obtained is as high as 99.9%, which can effectively prevent the aerogel material from absorbing moisture in the air and causing the material to crack or even collapse, thereby affecting the performance of the aerogel.
[0036] (5) The present invention provides a universal method for preparing low thermal conductivity insulation materials. By replacing the mold of the corresponding insulation material, insulation products of different shapes such as insulation boards and insulation covers can be obtained to meet the actual needs of personalized customization. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a physical picture of the thermal insulation flat plate layer prepared in Example 1 of the present invention.
[0038] Figure 2 This is a physical picture of the heat shield mold used in the preparation process of Example 2 of the present invention.
[0039] Figure 3 This is a physical picture of the heat shield prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0040] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0041] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art. Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0042] In the following embodiments, the thermal conductivity of the heat shield is tested according to GB / T 10294-2008, and the hydrophobicity is tested according to GB / T 10299-2011, and the specific test methods are not described in detail.
[0043] Embodiment 1:
[0044] This embodiment provides a lightweight flat thermal insulation layer with low thermal conductivity, and the specific preparation method is as follows:
[0045] (1) Gel test:
[0046] Prepare 4 mol / L ammonium fluoride solution: weigh 74g±1g solid ammonium fluoride in a 500mL beaker using an electronic balance, add 100mL deionized water and stir to completely dissolve it, then pour the solution into a 500mL volumetric flask, wash the beaker 3 times with a small amount of deionized water, pour the washing liquid into the volumetric flask, and when the liquid level in the volumetric flask is close to the scale line, use a rubber dropper to slowly add until the scale line. Cover the bottle with a stopper and shake well to mix the solution in the beaker evenly.
[0047] Take 1375g of 25% silicon solution, 41.25g of 1mol / L hydrochloric acid, and 41.25g of 4mol / L ammonium fluoride; slowly add the hydrochloric acid into the stirred silicon solution within 5 minutes, and stir for 5 minutes after completion; then slowly add the ammonium fluoride into the stirred mixed solution within 5 minutes, and stir for 5 minutes after completion.
[0048] (2) Dipping:
[0049] Spread the quartz fiber needle felt with a size of 300×300×10mm into a square mold of 325×325×50mm, and slowly pour the mixed gel solution in step 1 into the flat insulation layer mold to ensure that the fiber is fully impregnated. Seal the mold to prevent excessive evaporation of the liquid, and put it into an ultrasonic cleaner for 20 minutes (room temperature, power 3.9A×2) to exhaust the gas inside the fiber.
[0050] (3) Aging:
[0051] Take out the mold from the ultrasonic cleaner, let it stand at room temperature for 48±2h, put it in an 80℃ oven for 48±2h, and then take it out and cool it to room temperature.
[0052] (4) Solvent replacement:
[0053] Take the mold out of the oven, wait for the mold to cool to room temperature, disassemble the mold and take out the sample. Soak the sample in anhydrous ethanol (heat the soaking liquid to 55°C) 10 times (13750g) of the weight of the wet gel for 48 hours, repeat twice.
[0054] (5) Supercritical drying
[0055] Place the wet gel in a drying kettle, heat the drying kettle to 50±6℃, pressurize and maintain the pressure at 10-14MPa, allow CO2 to circulate between the drying kettle and the separation kettle, receive the separated ethanol solvent in the two separation kettles respectively, until no ethanol is discharged, continue to circulate for 3±0.54h, and then slowly release the pressure.
[0056] (6) Moisture-proof treatment
[0057] a. High temperature treatment
[0058] The dried aerogel insulation layer was weighed (390.45g), then placed in a high-temperature muffle furnace, heated from 50°C, 60min to 200°C, kept warm for 2h, then heated to 600°C for 90min, kept warm for 1h, and then naturally cooled to 100°C. The sample was taken out and weighed 376.36g. After trimming, the weight of the flat insulation layer was measured to be 345.72g. The sample thickness is 13.99mm, width is 30cm, length is 30cm, and density is 274.5kg / m 3 The thermal conductivity was measured to be 0.02048 W / (m·K).
[0059] b. Hydrophobic treatment
[0060] After the sample is treated at high temperature, it is placed on the vacuum tank partition, the cover is closed, and it is placed in a 100℃ oven for heating for 2h, evacuated to -0.08MPa, and the vacuum pump is turned off. Weigh 320g of trimethylmethoxysilane and suck it into the vacuum pump. Record the change in vacuum degree every 12h during the reaction. After 48h of reaction, take out the sample and place it in a ventilated place to cool to room temperature. Weigh 387.57g, then put it in an 80℃ oven for 30min and take it out. Place the sample in a ventilated place and let it stand for 5±0.5h to allow the organic reagent to evaporate, and weigh it until constant weight.
[0061] The measured weight is 384.56g, the thickness is 13.99mm, the width is 30cm, the length is 30cm, and the density is 305.3kg / m 3 The thermal conductivity is 0.02345 W / (m·K). The sample was cut into 30 cm×10 cm×1.4 cm to measure the hydrophobicity. The weight before and after the measurement was 128.32 g and 128.92 g, and the hydrophobicity was calculated to be 99.9%.
[0062] The sample was placed in a high-temperature muffle furnace and heated from room temperature to 500°C in 100 minutes. After being kept at this temperature for 2 hours, the sample was naturally cooled to room temperature. Figure 1 As shown, it is a square flat plate structure, the weight of the heat shield is 376.08g, the thickness is 13.87mm, and the density is 301.3kg / m 3 . Thermal conductivity: 0.02421W / (m·K).
[0063] Embodiment 2:
[0064] This embodiment provides a lightweight heat insulation cover with low thermal conductivity and a corresponding flat heat insulation layer, and the specific preparation method is as follows:
[0065] (1) Preparation of gel:
[0066] Take 25.514 kg of 25% silicon solution, 0.765 kg of 1 mol / L hydrochloric acid, and 0.765 kg of 4 mol / L ammonium fluoride, and prepare a gel solution by referring to the operation in Example 1.
[0067] (2) Dipping:
[0068] Spread the quartz fiber needle felt with the size of 300×300×10mm into a square mold with the size of 325×325×50mm, and spread the quartz fiber needle felt with the special shape into the mold. Figure 2 The mold shown in the figure (matching the shape of the heat shield) was poured into the molds. The mixed gel solution in step 1 was slowly poured into the molds to ensure that the fibers were fully impregnated. The molds were sealed to prevent excessive evaporation of the liquid and placed in an ultrasonic cleaner for 1.5 hours (room temperature, power 3.9A×2) to exhaust the gas inside the fibers.
[0069] (3) Aging
[0070] Take out the mold from the ultrasonic cleaner, let it stand at room temperature for 48±2h, put it in an 80℃ oven for 48±2h, and then take it out and cool it to room temperature.
[0071] (4) Solvent replacement
[0072] Open the mold, take out the sample, and soak the sample in anhydrous ethanol (heat the soaking solution to 55° C.) with a weight that is 10 times (120 kg) the weight of the silicon solution for 6 days, and repeat twice.
[0073] (5) Supercritical drying
[0074] Place the wet gel in a drying kettle, heat the drying kettle to 50±6℃, pressurize and maintain the pressure at 10-14MPa, allow CO2 to circulate between the drying kettle and the separation kettle, receive the separated ethanol solvent in the two separation kettles respectively, until no ethanol is discharged, continue to circulate for 3±0.54h, and then slowly release the pressure.
[0075] (6) Moisture-proof treatment
[0076] a. High temperature treatment
[0077] The dried aerogel insulation layer was weighed (443.8 g for the flat plate and 1843.9 g for the insulation cover), and then placed in a high-temperature muffle furnace, heated from 50°C to 200°C in 60 minutes, kept warm for 2 hours, and then heated to 600°C in 90 minutes. After keeping warm for 1 hour, the temperature was naturally lowered to 100°C, and the sample was taken out and weighed (424.6 g for the flat plate and 1787.0 g for the insulation cover).
[0078] After trimming, the flat plate weighs 377.15g, has a thickness of 14.45mm, a width of 30cm, a length of 30cm, and a density of 289.9kg / m3 The thermal conductivity was measured to be 0.02035 W / (m·K).
[0079] b. Hydrophobic treatment
[0080] After the sample is treated at high temperature, it is placed on the vacuum tank partition, the cover is closed, and it is placed in a 100°C oven and heated for 2 hours. It is evacuated to -0.08MPa and the vacuum pump is turned off. Weigh trimethylmethoxysilane (349+1602g) and suck it into the vacuum pump. The change in vacuum degree is recorded every 12 hours during the reaction. After reacting for 48 hours, take out the sample and place it in a ventilated place to cool to room temperature. After weighing (420.8g, 2127.4g), put it in an 80°C oven for 30 minutes and take it out (407.2g, 1971.2g). Place the sample in a ventilated place and let it stand for 5±0.5h to allow the organic reagent to evaporate, and weigh it until constant weight.
[0081] The weight of the flat thermal insulation layer finally obtained in this embodiment is measured to be 405.76g, the thickness is 14.47mm, the width is 30cm, the length is 30cm, and the density is 311.4kg / m 3 The hydrophobicity is about 99.9%, and the thermal conductivity is measured to be 0.02191 W / (m·K).
[0082] In summary, the present invention successfully obtains a lightweight thermal insulation material with low thermal conductivity and high hydrophobicity through the steps of gelation, dipping, aging, solvent replacement, supercritical drying, high temperature treatment, hydrophobic treatment, etc., which can achieve targeted thermal insulation and heat preservation on machinery and equipment in the fields of ships, aerospace, etc. The present invention can also obtain thermal insulation products of different shapes such as thermal insulation boards and thermal insulation covers by replacing the dipping mold of the corresponding thermal insulation material to meet the actual needs of personalized customization.
[0083] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing a lightweight thermal insulation material with low thermal conductivity, characterized in that: It includes the following steps: S1. Glue preparation: Add the acidic catalyst solution and the alkaline catalyst solution to the silica gel solution successively, and stir evenly to obtain a gel solution; S2. Fiber impregnation: Spread the fiber reinforcement flat in a mold, pour the gel solution prepared in S1 into the mold to fully impregnate the fiber reinforcement, degas and then seal and let it stand; S3. Aging: Heat up the mold after standing in S2 for aging; S4. Solvent replacement: Immerse the wet gel after aging in S3 in ethanol for solvent replacement at least twice; The relationship between the time of each solvent replacement and the thickness d of the wet gel is specifically: d < 10mm, soak for 1 - 2 days each time; 10 < d < 20mm, soak for 4 days each time; 20 < d < 25mm, soak for 6 days each time; 20 < d < 30mm, soak for 8 days each time; S5. Supercritical drying: Perform supercritical carbon dioxide drying on the wet gel after solvent replacement in S4 to obtain an aerogel thermal insulation layer; S6. Moisture-proof treatment: Perform gradient high-temperature treatment on the aerogel thermal insulation layer obtained in S5; Then place it in a vacuum environment, add a siloxane-based hydrophobic reagent for hydrophobic treatment, take it out and dry to obtain the thermal insulation material.
2. The method for preparing a lightweight thermal insulation material with low thermal conductivity according to claim 1, characterized in that: In step S1, the concentration of the acidic catalyst solution is 0.5 - 1.5mol / L, the concentration of the alkaline catalyst solution is 3 - 5mol / L, and the silicon content of the silica gel solution is 15 - 30%; The mass ratio of the silica gel solution, the acidic catalyst solution and the alkaline catalyst solution is 100:(2 - 4):(2 - 4).
3. The method for preparing a lightweight thermal insulation material with low thermal conductivity according to claim 1, characterized in that: In step S1, the acidic catalyst includes one or more of phosphoric acid, nitric acid, hydrochloric acid, sulfuric acid, acetic acid, oxalic acid or acetic acid; The alkaline catalyst includes one or two of ammonia water, sodium hydroxide, ammonium fluoride, ammonium carbonate, ammonium bicarbonate, ethylenediamine.
4. The method for preparing a lightweight thermal insulation material with low thermal conductivity according to claim 1, characterized in that: In step S2, the fibers in the fiber reinforcement include one or more of quartz fiber, basalt fiber, glass fiber or alumina fiber; The standing time is 40 - 60h.
5. The method for preparing a lightweight thermal insulation material with low thermal conductivity according to claim 1, characterized in that: In step S3, the aging temperature is 75 - 90°C, and the aging time is 40 - 60h; In step S5, the supercritical drying temperature is 40 - 60°C, and the pressure is 10 - 14MPa.
6. The method for preparing a lightweight thermal insulation material with low thermal conductivity according to claim 1, characterized in that: In step S6, the specific process of the gradient high-temperature treatment is: Heat up from 50°C to 200 - 250°C and keep warm for at least 2h, then heat up to 600 - 700°C and keep warm for at least 1h, and the heating rate is 2 - 5°C / min.
7. The method for preparing a lightweight thermal insulation material with low thermal conductivity according to claim 1, characterized in that: In step S6, the siloxane-based hydrophobic reagent includes one or more of trimethylmethoxysilane, trimethylethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, dimethylmethoxysilane, dimethylethoxysilane, methyltrimethoxysilane or methyltriethoxysilane; The time of the hydrophobic treatment is 40 - 60h.
8. A lightweight thermal insulation material with low thermal conductivity prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The thermal conductivity of the thermal insulation material is 0.020 - 0.025W / m·K.
9. A lightweight thermal insulation material with low thermal conductivity according to claim 8, characterized in that: The density of the thermal insulation material is 280-320 kg / m 3 , the water repellency of the thermal insulation material is not less than 99.5%.
10. Application of the lightweight thermal insulation material with low thermal conductivity described in claim 8 in the fields of aerospace, military industry and shipbuilding.
Citation Information
Patent Citations
High-performance thermal insulation material and preparation method thereof
CN101948296A
Ultralow-density silicon dioxide aerogel material and preparation method thereof
CN107021496A
High-temperature-resistant, heat-insulating wave-transmitting integrated aerogel composite material and preparation process thereof
CN111099912A
Wave-transmitting, efficient and heat-insulating aerogel composite material and preparation method thereof
CN112851292A
Cited By
Aerogel polycarbonate multi-structure heat insulation and sound insulation material as well as preparation method and application thereof
CN119974722A